Vocational Psychological Study of Students in Construction and Housing Engineering Vocational Competencies in Vocational Schools - Suwandi, Fakhri Fauzi; Basyirun, Basyirun (Journal of Vocational and Career Education, 2023)
Vocational psychology is a study or science that is applied in observing behavior in vocational education. The aim of vocational psychology is to determine vocational choices based on students' interests and talents. The Construction and Housing Engineering vocational competency aims to develop competency in the construction sector. Schools have demands to be able to fulfill aspects of providing adequate facilities and education so that Construction and Housing Engineering can carry out learning activities. In fulfilling DU/DI requests, Construction and Housing Engineering graduates must have good competencies. In fulfilling competencies for students, there are several psychological factors, namely internal and external factors. Internal factors in students are the student's personality, knowledge of the student's interests and talents, and aspirations. External factors are influenced by the social environment, family, school and place of residence.